The Role of Anaphase-Promoting Complex/Cyclosome (APC/C) in Plant Reproduction - Saleme, Marina de Lyra Soriano; Andrade, Ingrid Rocha; Eloy, Nubia Barbosa (Frontiers in Plant Science, 2021)
Most eukaryotic species propagate through sexual reproduction that requires male and female gametes. In flowering plants, it starts through a single round of DNA replication (S phase) and two consecutive chromosome segregation (meiosis I and II). Subsequently, haploid mitotic divisions occur, which results in a male gametophyte (pollen grain) and a female gametophyte (embryo sac) formation. In order to obtain viable gametophytes, accurate chromosome segregation is crucial to ensure ploidy stability. A precise gametogenesis progression is tightly regulated in plants and is controlled by multiple mechanisms to guarantee a correct evolution through meiotic cell division and sexual differentiation. In the past years, research in the field has shown an important role of the conserved E3-ubiquitin ligase complex, Anaphase-Promoting Complex/Cyclosome (APC/C), in this process. The APC/C is a multi-subunit complex that targets proteins for degradation via proteasome 26S. The functional characterization of Anaphase-Promoting Complex/Cyclosome (APC/C) subunits in Arabidopsis, which is one of the main E3 ubiquitin ligase that controls cell cycle, has revealed that all subunits investigated so far are essential for gametophytic development and/or embryogenesis.